A review on mitochondrial restorative mechanism of antioxidants in Alzheimer’s disease and other neurological conditions - Kumar, Anil; Singh, Arti (Frontiers in Pharmacology, 2015)
Neurodegenerative diseases are intricate in nature because of the involvement of the multiple pathophysiological events including mitochondrial dysfunction, neuroinflammation and oxidative stress. Alzheimer’s disease (AD) is a neurodegenerative disease explained by extracellular amyloid beta deposits, intracellular neurofibrillary tangles and mitochondrial dysfunction. Increasing evidence has indicated that mitochondrial dysfunction displays significant role in the pathophysiological processes of AD. Mitochondrial dysfunction involves alterations in mitochondrial respiratory enzyme complex activities, oxidative stress, opening of permeability transition pore and enhanced apoptosis. Various bioenergetics and antioxidants have been tried or under different investigational phase against AD and other neurodegenerative disorders (Parkinson’s disease, Huntington’s disease and Amyotrophic lateral sclerosis) because of their complex and multiple site of action. These mitochondrial-targeting bioenergetics and antioxidant compounds such as coenzyme Q10, idebenone, creatine, mitoQ, mitovitE, mitotempol, latrepirdine, methylene blue, triterpenoids, SS peptides, curcumin, Ginkgo biloba and omega-3 polyunsaturated fatty acids with potential efficacy in AD have been identified. Present review is intent to discuss mitochondrial restorative mechanisms of these bioenergetics and antioxidants as a potential alternative drug strategy for effective management of AD.